Development Of Wordwall-Based Educational Game Learning Media For Students At SDIT Al Mawaddah Warrahmah Kolaka - Yulfina Deki Yulfina; Nurhayati Nurhayati; Hartono Hartono (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to develop Wordwall-based educational game learning media for students at SDIT Al Mawaddah Warrahmah Kolaka and to determine its level of validity, practicality, and effectiveness in improving students’ learning interest and learning outcomes. This research employed a Research and Development (R&D) method using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The study was conducted at SDIT Al Mawaddah Warrahmah Kolaka from January to February 2026, involving elementary school students as research subjects. Data collection techniques included interviews, observations, teacher and student response questionnaires, and learning outcome tests. Data analysis was carried out through validity analysis, practicality analysis, analysis of teacher and student responses, and effectiveness analysis of the learning media. The results showed that the developed Wordwall learning media was categorized as valid, practical, and effective for classroom use. Student responses reached 85.41%, indicating that the media was feasible, while teacher responses reached 90.66%, indicating that the media was highly practical. Furthermore, the effectiveness test result showed a percentage of 68.75%, categorized as effective in improving students’ learning outcomes. Therefore, Wordwall-based educational game media can serve as an engaging and interactive instructional alternative to enhance students’ learning interest and academic achievement in elementary school.